2020
DOI: 10.1097/prs.0000000000006654
|View full text |Cite
|
Sign up to set email alerts
|

Direct-to-Implant, Prepectoral Breast Reconstruction: A Single-Surgeon Experience with 201 Consecutive Patients

Abstract: Background: The resurgence of prepectoral breast reconstruction has brought strict patient inclusion and exclusion criteria by numerous authors. This article provides an overview of a single surgeon’s experience with 201 patients, 313 breasts using immediate, direct-to-implant prepectoral breast reconstruction. The article compares surgical outcomes of different patient cohorts to elucidate risk factors that may predispose patients toward developing complications. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
49
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(50 citation statements)
references
References 28 publications
0
49
0
1
Order By: Relevance
“…Similar to previous reports in the literature, our subanalysis looking at the DTI group to compare subpectoral versus prepectoral DTI found no significant difference in ischemic outcomes. 27,28 Our analysis showed no ischemic complications in the prepectoral group as compared with a 15.8% mastectomy flap necrosis rate and an 15.8% partial NAC necrosis rate in the subpectoral group. This significant decrease in ischemic complications is likely a product of both breast and the plastic surgeons' efforts and refinements in technique.…”
Section: Discussionmentioning
confidence: 63%
“…Similar to previous reports in the literature, our subanalysis looking at the DTI group to compare subpectoral versus prepectoral DTI found no significant difference in ischemic outcomes. 27,28 Our analysis showed no ischemic complications in the prepectoral group as compared with a 15.8% mastectomy flap necrosis rate and an 15.8% partial NAC necrosis rate in the subpectoral group. This significant decrease in ischemic complications is likely a product of both breast and the plastic surgeons' efforts and refinements in technique.…”
Section: Discussionmentioning
confidence: 63%
“…5 Two more recent studies on ADM-assisted prepectoral DTI-IBR both reported PMRT not to significantly influence the rate of postoperative complications. 24 25 Still, we have been unable to trace an unambiguous recent report on the influence of PMRT on the short-term surgical outcome of non-ADM-assisted combined [N]SSM/SDTI-IBR.…”
Section: Discussionmentioning
confidence: 85%
“…3 If ADM was used, it was as a medium-thickness, fenestrated, anterior-only coverage of the implant without any chest wall fixation. 3 [See Video (online), which shows mastectomy dissection with flap thickness. ]…”
Section: Methodsmentioning
confidence: 99%
“…1,2 Prepectoral breast reconstruction has thus experienced a resurgence in popularity, because of a growing body of evidence demonstrating reliable clinical outcomes, limited complications, favorable economic profile, and enhanced patient recovery relative to the traditional, subpectoral approach. 1–3…”
mentioning
confidence: 99%